Pelatihan Pembuatan Permainan Edukasi Online Menggunakan Aplikasi QuizWhizzer untuk Meningkatkan Kecakapan Digital Guru - Delthawati Isti Ratnaningtyas; Sahrul Saehana; Ielda Paramita; Rudi Santoso (PELITA NUSA TENGGARA, 2026)
Teachers have commonly utilized existing online educational games to create more engaging learning experiences. However, their digital competence in developing online educational games remains insufficiently developed. QuizWhizzer is one of the digital applications that can be used to create online educational games. Therefore, this community service program aimed to (1) train teachers to use the QuizWhizzer application in developing online educational games, (2) improve teachers’ digital competence, and (3) examine teachers’ responses to the training program. The participants consisted of 34 teachers from SMPN 6 Palu. The program was conducted through three stages: preparation, implementation, and evaluation. The training activities included lectures, demonstrations, and hands-on practice in using the QuizWhizzer application. The results showed that the average pre-test score of teachers’ digital competence was 53.33, while the average post-test score increased to 72.94, with a normalized gain score of 0.44. In addition, 94.12% of the participants successfully completed the practical assignment of developing online educational games using QuizWhizzer. The average score of teachers’ responses to the training was 4.65, indicating a highly positive perception. Based on these findings, it can be concluded that (1) the teachers were successfully trained to use QuizWhizzer for developing online educational games, (2) their digital competence improved at a moderate level, and (3) they expressed highly positive responses toward the training program.